Digital Transformation of Local Government: Design and Development of the Pakuhaji District Community Service Information System Website - Mukti Budiarto; Ari Asmawati; Muhamad Kurniawan (International Institute for Advanced Science & Technology (IIAST), 2024)
In the era of digital transformation, local governments are increasingly pursuing innovation to improve the quality of public services. This research aims to carry out digital transformation in the government of Pakuhaji District, Tangerang Regency, by designing and building an efficient and responsive public service information system website. Through a systems development approach, this research identifies community needs, evaluates existing service processes, and designs information technology-based solutions. The designed information system covers various aspects of community services, such as submitting correspondence, public service information, and managing population data. The use of web technology enables better accessibility for the public, increases administrative efficiency, and speeds up the handling of service requests. The application of responsive design principles and intuitive interfaces is also a focus in website development to ensure optimal user experience. The research methodology includes a community needs survey, analysis of existing service processes, and development of a website prototype. It is hoped that the results of this research can make a positive contribution to the effectiveness and efficiency of community services in Pakuhaji District, creating a local government that is more responsive and connected to the needs of its citizens. It is hoped that this digital transformation can become the basis for further development in realizing a technology-oriented government for the welfare of society.